Collet-Sicard syndrome as a result of unilateral carotid artery dissection. (31st July 2013) - Smith, Rupert; Tassone, Peter; Saada, Janak
Abstract : A 52-year-old man presented with sudden onset symptoms of multiple cranial nerve palsies (IX, X and XII) following a 10-day history of coryzal illness. Follow-up examination established atrophy of the trapezius suggesting additional involvement of the spinal accessory nerve (XI). Further investigation including CT and MRI demonstrated dissection of the internal carotid artery. Given the involvement of cranial nerves IX to XII, and that the patient demonstrated no signs of Horner's syndrome, we suggested that this patient fits the description of Collet-Sicard syndrome. On vascular opinion the carotid dissection was expected to resolve without intervention but the patient was prescribed aspirin for thromboprophylaxis. Gradual resolution of neurological symptoms was observed at 8-week follow-up.